2014
DOI: 10.4067/s0718-58392014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seeding rate on grain quality of winter wheat

Abstract: Planting density is important factor which influence yield and quality of wheat (Triticum aestivum L.) For this reason, in scientific investigations is constantly investigated optimization of plant number per unit area. The objective of this study was to determine the influence of seeding rate in grain quality of winter wheat cultivars. The experiment was conducted with four winter wheat genotypes ('Ana Morava', 'Vizija', 'L-3027', and 'Perla') at the Small Grains Research Centre of Kragujevac, Serbia, in 3 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 24 publications
4
44
0
7
Order By: Relevance
“…Therefore, best performing genotypes of this study can be selected and incorporated for further breeding program. Similar findings have also been reported by Zecevic et al, (2009) andAmagai, et al, (2014).…”
Section: Resultssupporting
confidence: 81%
“…Therefore, best performing genotypes of this study can be selected and incorporated for further breeding program. Similar findings have also been reported by Zecevic et al, (2009) andAmagai, et al, (2014).…”
Section: Resultssupporting
confidence: 81%
“…This could have been influenced by different thermal conditions in the winter of 2012-2013, which encouraged the transition to the vernalization stage combined with the optimum distribution of precipitation. Zecevic et al (2014) confirmed the effect of weather conditions in the growing Sept periods on the analyzed parameters of the quality of wheat grain (proteins, gluten, and Zeleny index). After analyzing the technological indicators for the grain in the second year of the experiment, increases were found in protein content (8.9%), gluten content (29.0%), Zeleny sedimentation index (34.7%), bulk density (9.3%), and grain hardness (28.6%).…”
Section: Resultsmentioning
confidence: 59%
“…The reasons behind this deficit might be due to poor crop management, including seeding rates and the use of old cultivars. For achieving high yield and quality of wheat, it is necessary to use all the cultural practices completely and on time and adapt them to cultivars [5]. So, the aim of this study was to determine the effect of different seeding rates on the grain yield and quality of three bread wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%